2020
DOI: 10.1038/s41438-020-0299-z
|View full text |Cite
|
Sign up to set email alerts
|

The RhHB1/RhLOX4 module affects the dehydration tolerance of rose flowers (Rosa hybrida) by fine-tuning jasmonic acid levels

Abstract: Phytohormones are key factors in plant responsiveness to abiotic and biotic stresses, and maintaining hormone homeostasis is critically important during stress responses. Cut rose (Rosa hybrida) flowers experience dehydration stress during postharvest handling, and jasmonic acid (JA) levels change as a result of this stress. However, how JA is involved in dehydration tolerance remains unclear. We investigated the functions of the JA-and dehydration-induced RhHB1 gene, which encodes a homeodomain-leucine zipper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 79 publications
(104 reference statements)
0
11
0
Order By: Relevance
“…makuwa [110]. Previous studies have shown that the regulatory module of RhHB1/RhLOX4 could mediate a JA feedback loop, enhancing dehydration tolerance by fine-tuning bioactive JA levels in dehydrated rose flowers (Rosa hybrida) [111]. .…”
Section: Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…makuwa [110]. Previous studies have shown that the regulatory module of RhHB1/RhLOX4 could mediate a JA feedback loop, enhancing dehydration tolerance by fine-tuning bioactive JA levels in dehydrated rose flowers (Rosa hybrida) [111]. .…”
Section: Droughtmentioning
confidence: 99%
“…makuwa [110]. Previous studies have shown that the regulatory module of RhHB1/RhLOX4 could mediate a JA feedback loop, enhancing dehydration tolerance by fine-tuning bioactive JA levels in dehydrated rose flowers (Rosa hybrida) [111]. Some NAC TF family members such as VvNAC17 and VvNAC26 in Vitis amurensis, have also been shown to regulate endogenous JA synthesis and upregulate other stress-responsive genes, thereby playing a positive role in drought tolerance [112,113].…”
Section: Droughtmentioning
confidence: 99%
“…The mixed bacterial solution of the TF and promoter cultures (2:1) for the induction analysis was used to infiltrate N. benthamiana leaves. After 48 h, the LUC fluorescence of the infiltrated leaves was detected, and LUC and REN activities were measured using luciferase reporter assay reagents (Promega) as described by a previous study 74 . Three replicate experiments were used for statistical analysis by Student’s t test.…”
Section: Methodsmentioning
confidence: 99%
“…The study has observed that RhHB1 binds to the RhLOX4 promoter to suppress its expression in the cut rose (Rosa hybrida). As a result, dehydration tolerance decreases (Fan et al, 2020). These genes were identified, while most genes were up-regulated under drought stress.…”
Section: Phytohormone Signals Under Drought Stressmentioning
confidence: 97%